Optimizing Sustainable Tourism Management In Saribu Gonjong Village, West Sumatra - Feronika Berutu; Rifdatul Husna; Graciella Natasha (Politeknik Internasional Bali, 2025)
Sustainable tourism can serve as a means to establish a positive relationship between tourism activities and the local environment. It encompasses three key dimensions: physical environment, socio-cultural sustainability, and economic sustainability. Optimizing the sustainable management of tourism at tourist destinations is essential. One such destination in West Sumatra is the Saribu Gonjong Tourism Village (SARUGO), located in Sorong Sungai Dadok Village, Kanagarian Koto Tinggi, Gunung Omeh Subdistrict, Lima Puluh Kota Regency. This tourism village is known for its authentic Minangkabau way of life, situated amidst lush green nature and featuring traditional houses that reflect the grandeur of Minangkabau architecture. In addition, Saribu Gonjong offers cultural attractions such as traditional Minangkabau dance performances. The tourism potential of Saribu Gonjong Village needs to be optimized through sustainable management practices. However, current tourism management efforts are still suboptimal and require a stronger emphasis on sustainability principles. This study employs a descriptive method with a qualitative approach, utilizing both primary and secondary data. Data collection techniques include in-depth interviews, participatory observation, and documentation. The collected data are analyzed through three stages: data reduction, data presentation, and conclusion drawing. To ensure data validity, data and source triangulation methods are applied. The research findings show that the increase in visits to Sarugo Tourism Village is achieved through collaborative promotion and annual cultural events. Challenges in accessibility and craft marketing are addressed through community self-initiatives, although government support remains necessary. From an environmental perspective, the village promotes awareness of cleanliness, cultural values, and mutual cooperation. Economically, positive contributions have begun to emerge, although they are limited by the fluctuating number of visitors. The potential of local businesses and agrotourism still requires strengthened promotion and service improvement. Socially, community training and cultural preservation efforts are in place, but remain limited and need to be expanded.